Fracture toughness and microstructural analysis of rotary friction welded S355J2 and SS316L steels for critical applications - Rajkumar Das; Giribaskar Sivaswamy; Himanshu Lalvani; Ajit Pal Singh (Journal of Advanced Joining Processes)
Dissimilar metal welding is seeing growing adoption across industries to enhance structural functionality and efficiency. Achieving high-quality, defect-free dissimilar weld joints requires a comprehensive understanding of the interrelationships between the welding-induced microstructural changes and the material's performance characteristics, particularly its fracture-related properties. This study investigates the impact of microstructural changes on the fracture toughness of dissimilar welds between structural low-carbon steel (S355J2) and austenitic stainless steel (SS316L) prepared using the Rotary Friction Welding (RFW) technique. Welding preforms were created from respective pipe pup pieces. The evaluation involves microstructural analysis, tensile testing, hardness testing, and fracture toughness testing using compact tension specimens derived from various zones of the weld joints. Results revealed significant microstructural differences across the weld joint. The weld region exhibited stable hardness with a maximum of 208 HV1 in S355J2′s thermo-mechanically affected zone (TMAZ). High tensile strength (Ultimate Tensile Strength 540 MPa, Yield Strength 367 MPa) with failures mainly on the S355J2 side. The fracture toughness (KQ) matched parent metal values, with the RFW weld centre line (WCL) showing superior crack tip opening displacement (CTOD) of 0.35 mm. Fractography generally indicates ductile failure.